Deadpool kills the Marvel universe one last time - Bunn, Cullen (Marvel Worldwide, Inc., 2025)
Cullen Bunn and Dalibor Talajic reunite to complete their chart-topping Deadpool Kills Trilogy! THE MARVEL MULTIVERSE IS IN DEADPOOL'S SIGHTS You loved it when Deadpool killed the Marvel Universe. You couldn't believe your luck when Deadpool killed the Marvel Universe again! Now, brace yourselves -- because Deadpool is about to kill the Marvel Universe...one...last...time! But we meet the murderous Merc with a Mouth at a low ebb -- alone, broken, bereft of purpose. Far from the sassin' assassin we know and love -- until a multiversal explorer arrives with a mission across realities that only Deadpool can complete. He has a kill list filled with familiar and surprising versions of your favorite heroes, and teleporting tech that can take him from universe to universe -- so it's time to get bodyslidin' and body-pilin'! Wade is back on the hunt -- and it's Marvels season!